Journal of Spices and Aromatic Crops: a Bibliometric Appraisal - Senthilkumaran, P.; Vadivel, V. (Journal of Information and Knowledge, 2014)
Bibliometric study of the 'Journal of Spices and Aromatic Crops' for the period 1992- 2000 is analyzed to understand the various characteristics of literature on the subject. Based on collected data, the study attempts to examine the year wise distribution of articles, authorship pattern, length of articles, subject wise breakup of articles and leading authors. Some inferences are also suggested based on the output of the analysis.